Improvement of localization with artificial landmark for mobile manipulator. (18th July 2019) - Guo, Shuai; Yan, Zhong-Xiang; Song, Tao; Xu, Zhen; Zeng, Ling-Dong
A method is presented for improving the localization accuracy of a mobile manipulator. The system consists of an industrial manipulator mounted on a mobile platform to perform fuselage drilling/riveting tasks in indoor environment. The localization is based on dual laser range finders mounted on the system and a number of artificial landmarks preset in the environment. Localization based on trilateration method is presented in this study. The adaptive unscented Kalman filter method is used to improve the accuracy of localization as well. The proposed method has been verified through experiments and the localization accuracy of mobile manipulator can be improved to 8 mm in most cases.